2012
DOI: 10.1111/ejh.12006
|View full text |Cite
|
Sign up to set email alerts
|

Hypoalbuminaemia is an independent predictor for hemophagocytic lymphohistiocytosis in childhoodEpstein–Barr virus‐associated infectious mononucleosis

Abstract: Hypoalbuminaemia is a unique characteristic and potentially a valuable predictor for HLH in paediatric EBV-associated IM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
8
1
Order By: Relevance
“…Hypoalbuminemia is generally considered as an indicator of malnutrition. Previous studies have found that hypoalbuminemia was related to the inferior outcomes in HLH [16,[36][37][38]. However, there is no relationship between the albumin level and patient survival among our cohort.…”
Section: Discussioncontrasting
confidence: 64%
“…Hypoalbuminemia is generally considered as an indicator of malnutrition. Previous studies have found that hypoalbuminemia was related to the inferior outcomes in HLH [16,[36][37][38]. However, there is no relationship between the albumin level and patient survival among our cohort.…”
Section: Discussioncontrasting
confidence: 64%
“…Huang et al reported that hypoalbuminemia is an independent predictor for HLH in childhood EBV‐associated disease . Taken together, these findings suggest that every patient with EBV‐HLH should be treated with a tailored therapeutic strategy based on the laboratory findings at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 93%
“…Secondly, different study objects from previous reports could be another reasonable explanation. Previous reports only included patients younger than 18-year old6-7,9,11-12 or in university students 13-14. We collected patients with confirmed diagnose of IM at all ages, hospitalized in paediatrics department and non-paediatrics department.…”
Section: Discussionmentioning
confidence: 99%